Analisis Perspektif Keuangan, Pelanggan, Proses Bisnis Internal, Pembelajaran dan Pertumbuhan Terhadap Kinerja Koperasi Konsumen Karyawan RS Kasih Ibu Surakarta dengan Menggunakan Pendekatan Balanced Scorecard - Dewi Saparini; LMS Kristiyanti; Rukmini (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2026)
This study examines the effect of the four Balanced Scorecard perspectives on the financial performance of the Employee Consumer Cooperative of Kasih Ibu Hospital Surakarta. Using a quantitative explanatory approach, data were collected from 87 cooperative members selected through the Slovin formula and analyzed using multiple linear regression. The results indicate that the financial perspective and internal business process perspective have a significant positive effect on financial performance, whereas the customer perspective and learning and growth perspective do not show a significant effect. The proposed model explains 81.6% of the variation in the cooperative's financial performance. These findings provide additional empirical evidence on the application of the Balanced Scorecard in consumer cooperatives and suggest that financial management and internal business processes remain important considerations for improving cooperative performance.